Analisis Pertanggung Jawaban Pidana terhadap Pelaku Pemalsuan Merk: (Studi Putusan Nomor : 381/Pid.Sus/2023/PN.Tjk) - Lovely Ardhanes Wira; Diah Gustiniati Maulani; Emilia Susanti (Majelis: Jurnal Hukum Indonesia, 2025)
The government’s efforts to provide protection for trademark rights holders have been implemented by enacting and updating laws on trademarks. However, in reality, crimes against trademark rights continue to occur, including in the jurisdiction of the Tanjung Karang District Court. This research addresses the following issues: What are the judges' considerations in cases of unauthorized use of registered trademarks, and how is the criminal analysis of such offenses reflected in Decision Number: 381/Pid.Sus/2023/PN.Tjk? This study uses normative and empirical legal research methods, with statutory and conceptual approaches. The data type used is secondary data obtained through literature study. Data processing involved selection, classification, and organization. The data were analyzed using a descriptive qualitative method. The findings of this research indicate that the judge's legal basis in sentencing the defendant for the unauthorized use of a registered trademark in Decision Number: 381/Pid.Sus/2023/PN.Tjk includes juridical considerations—specifically that the defendant was legally and convincingly proven to have committed a criminal offense as regulated under Article 100 paragraph (1) of Law Number 20 of 2016 concerning Trademarks and Geographical Indications. Philosophically, the judge considered the imposed sentence as a means of rehabilitation and deterrence. Sociologically, the judge weighed both aggravating and mitigating factors in the sentencing. Criminal liability for the offender was based on the fulfillment of criminal responsibility elements, namely that the defendant was an adult and legally capable of committing the act. The element of fault was fulfilled, as the defendant knowingly and intentionally used a registered trademark without authorization, fully aware that such an act constitutes a criminal offense. The element of the absence of justification or excuse was also met, as the defendant committed the offense in a conscious and sound state of mind, without coercion.